Factors That Influence The Intention of The Millennial Community to do Waqf With a Modification of Theory Planned Behavior Approach - Zawawi, Abdullah Achmad; Mariyanti, Tatik; Sari, Siti Nurindah (APTISI Transactions on Management (ATM), 2023)
This research aims to analyze the influence of variables knowledge, attitudes, religious commitment, subjective norm, and the use of ICT Technology significantly influence behavior through the intention of the millennial generation in waqf in Jabodetabek. The methodology used in this study is the Structural Equation Model with the variables of knowledge, attitudes, religious commitment, subjective norms, and ICT technology as independent variables; intention as moderating variable, and waqf behavior as the dependent variable. The primary data of this study was obtained through a questionnaire survey to 290 respondents obtained through purposive random sampling from the millennial generation aged 21-40 years who live in Greater Jakarta. Then the data was analyzed using SPSS and AMOS software. Based on the results of this study, it was learned that the variable of knowledge does not affect the behavior of waqf through the intention of the millennial generation. In contrast, the variables of attitude, commitment, subjective norms, and the use of ICT technology had a positive and significant effect on waqf behavior through the intention of the millennial generation. This shows that the millennial generation, although their knowledge does not affect behavior, attitudes, commitment, subjective norms, and the use of ICT technology, have a positive and significant effect on waqf behavior results of this study indicate that the variables attitudes, religious commitment, subjective norm, and the use of ICT Technology significantly influence behavior through the intention of the millennial generation in waqf in Jabodetabek. At the same time, knowledge does not affect that behavior. This study implies that measuring consumer behavior should be equipped with additional indicators, namely intention, to analyze the behavior based on external factors and spiritual and social aspects.